Continuous 500-Hz OH-PLIF Measurements in a Hydrogen-Fueled Scramjet Combustor - Peng, Jiangbo; Cao, Zhen; Yu, Xin; Yang, Shunhua; Yu, Yang; Ren, Hongyu; Zhang, Shunping; Chang, Guang; Chen, Shuang; Zhao, Yanhui; Yan, Biao; Luo, Ye (Frontiers in Physics, 2020)
In recent years, significant research attention has focused on scramjet bench-testing using optical measurement techniques to obtain significant experimental data. The work aims to verify the environmental reliability of high-speed planar laser-induced fluorescence (PLIF) technique and satisfy bench-test requirements. A high-speed OH-PLIF system with 1.8 mJ/pulse at 500 Hz is developed, and tests are conducted at a direct-connect supersonic combustion facility. In this paper, OH-PLIF signals and pressure were measured simultaneously, and flame dynamics during pressure buildup were investigated, with a special focus on the ignition and flameout processes. In addition, the flame trajectory of the ignition process is depicted. The results show that the time scale of flame development is consistent with that of pressure stability, whereas the pressure change lags the change in flame intensity. The flame structure is discussed in both scramjet and ramjet modes. An unstable flame structure develops in the ramjet mode, and the flame area decreases similarly in both combustion modes. Flame oscillations are captured for three hydrogen equivalence ratios.